The reference to Spanish law in matters of succession and matrimonial economic regime - Iglesias Buigues, José Luis (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
This article deals with the non-pacific question of the application of the Spanish law in cases of succession and matrimonial property regimes given the content of the new Regulations (EU) 650/2012 and 2016/1103 and specifically taking into account how they deal with territorial multi-unit States, as it is the case of Spain. Given the fact that the application of Spanish law follows the principle of “unity of solutions”, i.e. the application of the same set of rules for both for international and merely and purely interregional cases –dispositions contained in Chapter IV of the Preliminary title of the Spanish civil Code–, some authors consider that some of these latter rules are still applicable despite they have been amended by the European legislator. The article critically analysis this doctrinal position and considers there is a better way for interpretation. However, both of them consider the necessity of a new system of internal conflict-of-law rules drafted by the Spanish legislator and given the new and current scenario.
Keywords: Succession and matrimonial economic regime; Regulations (EU) 650/2012 and 2016/1103; referral to the law of a plurilegislative State; conflits of domestic and international laws